Sifat fisikokimia dan formulasi tepung biji durian (Durio zibethinus Murr.), tepung biji pepaya (Carica papaya), dan aplikasinya dalam crispy cheese cookies: Physicochemical properties and formulation of durian seed flour (Durio zibethinus Murr.), papaya seed flour (Carica papaya), and their application in crispy cheese cookies - Sutanto, Tiffany Arista; Dealyn, Devondra Christabella Glenys; Sukweenadhi, Johan; Purwanto, Maria Goretti M. (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Wheat flour is usually used in food products. Wheat flour consumption and import costs in Indonesia are quite high. The idea of using fruit by-products to substitute wheat flour has the potential to reduce health and environmental problems. Because many fruit by-products contain beneficial nutrients and bioactive compounds, it might also become a solution for those with celiac disease because they are gluten-free. Both durian seeds and papaya seeds are abundantly available in Indonesia as a tropical country, so both can be made into fruit by-product flour. This study aims to evaluate the physicochemical properties of durian seed flour and papaya seed flour, the best formulation of composite flour made from wheat flour, durian seed flour, and papaya seed flour to make crispy cheese cookies, and the organoleptic characteristics of the cookies made from the composite flours. Randomized Group Design was applied with the following parameters: Yield, color, bulk density, water activity, proximate, crude fiber, dietary fiber, starch, shelf life, and organoleptic characteristics. The study showed that based on the physicochemical properties and highest organoleptic score, the best flour composition for crispy cheese cookies is F3 (50% wheat flour: 40% durian seed flour : 10% papaya seed flour). Durian seed flour and papaya seed flour are proven potential to be formulated and used to make crispy cheese cookies.